The DPRK: Just another Country - Weston, Chris (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The paper notes that up until 1973 both North and South Korea had essentially comparable GDP per capita. Thereafter, it is argued that choices made by the DPRK were substantially influenced by recent history in terms of concentrating on the nuclear and ballistic missile programmes in order to meet the perceived need for security which overrode other possible choices. The development of the country`s natural resources – whether energy, mineral reserves and the potential of the populace – have mitigated the sanctions regime in place since 1948. This paper argues that, when considering North Korea, history is “everything” and has influenced the economic choices and development of the country
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 486, s. 114-126
Keywords: North Korea; political economy; economic history; path dependency; Korea Północna; ekonomia polityczna; historia gospodarcza; łańcuch zależności